Mecanismos de trincamento por fadiga em revestimentos asfálticos reforçados com geogrelhas: interação entre aderência de interface e rigidez do reforço - Santos, Karolina Maria dos (Universidade Federal de São Carlos, 2026)
The incorporation of geosynthetic reinforcements at the interface between asphalt layers has been widely adopted as a strategy to extend pavement service life, contributing to the reduction of permanent deformation, the improvement of fatigue resistance, and the mitigation of reflective crack propagation. In this context, numerous studies have been conducted to better understand the mechanical behavior of reinforced asphalt systems and to provide guidance for the appropriate selection and design of these materials. In particular, the literature has extensively discussed the effects of geosynthetic reinforcement inclusion on flexural performance and interface bonding conditions between asphalt layers. However, significant knowledge gaps still remain regarding the mechanisms governing the effectiveness of these reinforcements throughout the pavement service life. In particular, there is a need for a deeper understanding of the interaction between interface bonding and reinforcement stiffness, as well as the influence of these parameters on the initiation, evolution, and propagation of damage within reinforced asphalt systems. This limitation hinders the advancement of mechanistic approaches and the development of rational design methods for geogrid-reinforced asphalt pavements. In this context, the present study investigates the combined influence of interface bonding and geogrid stiffness on the fatigue performance of reinforced asphalt systems at different stages of their service life, using Digital Image Correlation (DIC) as a strain-fieldbased evaluation tool. For this purpose, an 80 m experimental section was constructed on SP-225 State Highway, comprising one unreinforced segment and three reinforced sections using polyester (G-PET), polyvinyl alcohol (G-PVA), and fiberglass (G-FV) geogrids. Specimens extracted from the field section were tested in the laboratory through Leutner-type interlayer shear tests and four-point bending fatigue tests (4PBT) under cyclic loading with DIC monitoring. The present study has advanced the understanding of the mechanisms governing the fatigue of asphalt pavements reinforced with geogrids, demonstrating that structural performance results from the interaction between interlayer bonding, reinforcement properties, and loading levels. The results highlight that the analysis of these systems under cyclic loading requires an integrated approach, combining traditional fatigue parameters, improvement factors, and image-based analysis via DIC. This integration was essential to explain results that might appear contradictory when evaluated in isolation. Four primary crack reflection mechanisms were identified. The results indicated that the effectiveness of the reinforced systems depends on the loading level, with improved performance observed at the lower load levels tested, which are more representative of actual pavement service conditions. The effectiveness of the reinforced systems was found to be strongly dependent on maintaining adequate levels of interlayer bonding, which is essential for the mobilization of the reinforcement and the transfer of stresses throughout the loading process. The study concluded that interface bonding is the key parameter governing reinforcement mobilization and the resulting performance gains, controlling the efficiency of crack mitigation systems regardless of the stiffness of the reinforcement employed. Overall, the performance of these systems cannot be attributed to a single isolated parameter, but rather to the complex interaction among geosynthetic stiffness, interface shear strength, applied stress level, and the evolution of damage mechanisms throughout the service life of the pavement structure.
Fatigue cracking mechanisms in geogrid-reinforced asphalt pavements: interaction between interface bonding and reinforcement stiffness
Keywords: Pavimento reforçado; Geogrelha; Aderência de interface; Flexão em quatro pontos; Correlação de Imagem Digital (DIC); Fadiga; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA; 9. Indústria, Inovação e Infraestrutura